Transfer of polyantimony units. Issue 28 (23rd June 2021) - Heinl, Veronika; Seitz, Andreas E.; Balázs, Gábor; Seidl, Michael; Scheer, Manfred
Abstract : The synthesis and characterization of the unique polyantimony complex [(Cp′′Zr)2 (μ, η 1:1:1:1:1:1 -Sb6 )] (1 ) is described. Compound 1 was used as antimony source to transfer Sb n units to late transition metal fragments [Cp R M] (M = Fe, Co, Ni). Abstract : Transfer reagents are useful tools in chemistry to access metastable compounds. The reaction of [Cp′′2 ZrCl2 ] with KSb(SiMe3 )2 leads to the formation of the novel polyantimony triple decker complex [(Cp′′Zr)2 (μ, η 1:1:1:1:1:1 -Sb6 )] (1, Cp′′ = 1, 3-di-tertbutyl-cyclopentadienyl), containing a chair-like Sb6 6− ligand. Compound 1 represents a valuable transfer reagent to form novel antimony ligand complexes. Thus, the reaction of 1 with Cp R -substituted transition metal halides of nickel, cobalt and iron leads to the formation of a variety of novel Sb n ligand complexes, such as the cubane-like compounds [(Cp′′′Ni)4 (μ3 -Sb)4 ] (2 ) and [(Cp′′′Co)4 (μ3 -Sb4 )] (3a ) or the complexes [(Cp Bn Co)3 (μ3 -Sb)2 ] (4 ) and [(Cp′′′Fe)3 (μ3 -Sb)2 ] (5 ), representing a trigonal bipyramidal structure. Moreover, beside the transfer of Sb1 units, also the complete entity can be transferred as seen in the iron complex [(Cp′′′Fe)3 (μ3, η 4:4:4 -Sb6 )] (6 ). DFT calculations shed light on the bonding situation of the products.